Effect of Covid-19 lock down on domestic meat trade and consumption of meat and meat products in India - Narendra Babu, R; Ezhilvelan, S; Serma Saravana Pandian, A; Vanathi, A`; Vasanthi, C; Ramani, R (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This paper deals with survey of the impact of COVID-19 on domestic meat trade and consumption of meat and meat products in India. The survey has a specific focus on the domestic trade of meat and meat products during the pandemic COVID-19 lock down and was conducted by preparing a questionnaire and uploaded in google form and communicated to the respondents through email/Whatsapp. Based on the response offered by the respondents it appeared that during April and May 2020, there were likely to be widespread meat and meat product shortages in country due to difficulties associated with functioning of slaughter houses, availability of labours and supply of food animals. During COVID-19 lockdown period only 50 % of panchayat/municipal slaughter houses functioned of which nearly 81% of slaughterhouses functioned, occasionally, while 100 % of them had restricted working hours and 58.6 % restricted availability of skilled and 53.6 % restricted availability of unskilled labours. Moreover, movement of animals, raw materials were mostly restricted due to pandemic situation COVID-19. This disrupted the supply of meat and meat products to the consumers. Due to this there were changes in the wholesale rate of different types of meat especially on the rate of beef, mutton and chevon. There were also changes in the attitude of the consumer towards the purchase of hygienic and safe consumption of meat. The consumers also preferred to purchase the meat through online meat traders as restriction for migration of people prevailed during that time. Due to these factors the organized meat and poultry retail outlets have witnessed increased growth in sales. The domestic meat trade in India was adversely affected and suffered as an impact of COVID-19 lockdown.